Chemoselective generation of acyl phosphates, acylium ion equivalents, from carboxylic acids and an organophosphate ester in the presence of a Brønsted acid. Issue 9 (13th January 2017) - Sumita, Akinari; Otani, Yuko; Ohwada, Tomohiko
Abstract : Reactions of an organophosphate ester with carboxylic acids proceeded smoothly and chemoselectively in the presence of a Brønsted acid, affording acyl phosphate intermediates, leading to formation of various functional aromatic ketones. Abstract : We describe the chemoselective conversion of carboxylic acids to functional aromatic ketones promoted by a tailored organophosphate ester in the presence of a Brønsted acid. The protonated phosphate ester reacts with the carboxylic acid to form acyl phosphate, which reacts with benzenes to give aromatic ketones, probably through the acylium ion or its equivalent. The reaction time is short even at room temperature, and the reaction is compatible with various other functional groups, including amines, olefins, esters, amides and nitriles.